STUDI TENTANG VARIASI METODE PEMBELAJARAN PADA MATA PELAJARAN FIQIH DI MI MUHAMMADIYAH 10 KARANG ANYAR - Ulfa Nur Inayah; Muhammad Taqqiyuddin; Wandi Syahindra (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was motivated by a problem in the fiqh learning process for class V C at MI Muhammadiyah 10 Karang Anyar, the method implemented by the teacher in teaching only referred to one learning method, namely the lecture method. Thus, the learning process tends to be monotonous and ineffective. Meanwhile, in realizing an effective learning process, several variations of learning methods are needed to support the success of the learning. For this reason, it is important to carry out this research to find out how the methods vary at MI Muhammadiyah 10 Karang Anyar. This research aims to describe and analyze how high the implementation and level of success in implementing the variations in learning methods are. This research is descriptive-qualitative in nature with data collection methods carried out through observation, interviews and documentation. Testing the validity of this research data uses data source triangulation techniques and data collection method triangulation. The results of this research show that, 1) the implementation of class V C fiqh learning at MI Muhammadiyah 10 Karang Anyar has used quite varied learning methods. The various forms of learning methods implemented are: first, lecture method, second, question and answer method, third, discussion method, fourth, recitation method, fifth, practice method, sixth, talking stick method, seventh, example non example method, eighth, short card method. . 2.) the implementation of learning from planning to implementation has been good, but the evaluation of learning methods carried out by teachers is less than optimal and the process of implementing learning in Fiqh subjects at MI Muhammadiyah 10 Karang Anyar has used quite varied learning methods, namely using more than two or three learning methods in one learning process. The application of various methods applied during the learning process is through planning, use and evaluation. 3.) In implementing this learning method, it cannot be separated from the factors that encourage fiqh teachers to run smoothly in the learning process, including: a. teacher's determination in applying the method, b. learning resources, c. media facilities or equipment, d. learning atmosphere